Percussion Graphs: An Automaded Approach for Percussion Composition - Lopes, Louis Philippe Simões Castelo Branco (2011)
The evolutionary and generative art world isn’t a relatively new concept, and already has a great thriving community, who are passionate about art and its integration within an artificial computational mold. The solution to this problem isn’t a one-way street, with the community presenting various creative solutions to the problem including swarm types,genetic types, multi-agent types, neural networking types, cellular automata types and hybrids (a system that uses multiple types).